Resposta do cafeeiro (Coffea arabica L.) à lâminas de irrigação por gotejamento - Silva, César Antônio da (2007)
This study evaluated coffee plant Ruby, line MG-1192, vegetative development, yield and berry quality, cultivated under irrigation levels during five years. The experiment was done in a loamy red latosol, at Experimental Farm of Glória, located to 18º58 S and 48º12 W, and approximately 890 m above sea level, in the county of Uberlândia, in Minas Gerais, Brazil. The local climate is Cwa, with dry winter and hot and rainy summer. The experimental design was randomized blocks with four repetitions and eight treatments of irrigation levels, which were 0% (without irrigation), 30%, 60%, 90%, 120%, 150%, 180% and 210% of the Evaporation measured in the Class A tank (ECA). Planting was done in January 2001, at the spacing 3.5 m between rows and 0.7 m between plants. The plots consisted of three rows with eight plants each, and the four central plants of the middle row were evaluated. A drip irrigation system was used, with self compensating drippers at a flow of 3.5 L h-1, and the irrigations were always done on Mondays, Wednesdays and Fridays. Data on rainfall, water evaporation in Class A tank, temperature and air relative humidity were collected daily. Production fertilization was done conventionally under the plant canopy, while the micronutrients were applied as foliar sprays. Pest, disease and weed control was done as required. Weeds were cut with a weeder between rows and controlled with herbicides under the plant canopy. Plant height, canopy and stem diameter, length of the plagiotropic branches and number of internodes in the orthotropic branches were measured yearly (from 2002 to 2006). Starting in 2003, for four consecutive harvests, production, yield and profitability, and in 2006, the berry quality were evaluated. Regarding the coffee plant vegetative development, the best results were obtained with levels varying from 136.3% to 149.2% ECA. The maximum yield obtained was 115 60-kg sacs per hectare, obtained in 2004, with the level of 164.1% ECA. The irrigation did not mitigate the biannual effect, since, in 2005, yield was relatively low. However, the use of this technique reduced the percentage of big berries (sieves 19, 18 and 17) and it increased the number of medium berries (sieves 16 and 15), not interfering in the quality of coffee beverage.